Feasibility study of catfish cultivation business using independent feed using maggot - Prasetyo, Bayu Dwi; Gandhy, Abel (Jurnal Mantik, 2025)
This research was conducted with the aim of determining the financial feasibility of cultivating catfish using an artificial feed using maggot as source of protein. The indicators used in analyzing financial feasibility are Net Present Value (NPV), Internal Rate of Return (IRR), Break Event Point (BEP), Payback Period (PP), and Benefit Cost Ratio (B/C Ratio). The results of the business feasibility analysis on catfish cultivation are feasible because they meet the criteria that have been applied, namely the NPV with a value of IDR. 3,253,672, an IRR value of 94.58%, a net B/C value of 2.81, a payback period of 1 year and 1 month, and a BEP of 171 kg. The results of the analysis show that cultivating catfish using artificial feed is feasible in all indicators. Therefore, the recommended strategy to increase the advantages of using artificial feed with maggot as source of protein is to provide education and training to the public on how to make and produce artificial feed with maggot as protein source